Games Online dan Katarsis Virtual - Keken Frita Vanri; Benni Yusriza Hasbiyalloh (Universitas Multimedia Nusantara, 2012)
Interactivity, digitality, and virtuality are three important aspects of Internet technology, among others. Thanks to its break-through characteristics, internet brings many changes into the lives of people. Due to its accessible features and loads of information, many people's needs on information, entertainment and social interaction are necessarily answered. One of the most interesting and widely developed features on internet is online game. Online game promises its users the ability to connect with other fellow users in real time. This paper intends to view online game as a second reality, different with the real world we live in. By employing psychoanalysis theory initiated and developed by Sigmund Freud, this paper sees online game as a playing field for human Id (Freudian biological desire), constantly repressed in real world due to its persisting conflict with ego and super ego. Online game commonly perceived as